Association between Toxoplasma gondii and systemic lupus erythematosus: A systematic review and meta-analysis - Pierce Bassett; Brinley N. Zabriskie; Ashley Catchpole; Dawson Hedges (Journal of Translational Autoimmunity, 2022)
Infecting approximately one-third of the world's population, the intraneuronal parasite Toxoplasma gondii has been associated with several autoimmune diseases. While Toxoplasma gondii may be protective against multiple sclerosis, other findings have negatively associated Toxoplasma gondii with different autoimmune diseases, including systemic lupus erythematosus. To further characterize the association between Toxoplasma gondii and systemic lupus erythematosus, we completed a systematic review and meta-analysis of published studies looking at the association between Toxoplasma gondii and systemic lupus erythematosus. The primary results of a random-effects model showed an odds ratio of 2.34 (95% confidence interval 1.17–4.69, P = 0.017), indicating the odds of Toxoplasma gondii seropositivity were 2.34 times higher in the group with systemic lupus erythematosus than in the healthy control group. Few available source studies, an overall lack of information about immunosuppressive status, and little information about sex composition and assays limit this finding and indicate the need for additional research to further characterize the association between systemic lupus erythematosus and Toxoplasma gondii.